Does slow and steady win the race? Rates of antipsychotic discontinuation, antipsychotic dose, and risk of psychotic relapse - McCutcheon, RA; Taylor, D; Rubio, J; Nour, J; Pillinger, T; Murray, RM; Jauhar, S (Oxford University Press, 2023)
Background Antipsychotics are recommended for prevention of relapse in schizophrenia. It is unclear whether increased risk of relapse following antipsychotic discontinuation is predominantly associated with an absolute magnitude of dose reduction or rate of antipsychotic reduction. Establishing the responsible mechanism is important because prolonged withdrawal schedules have been suggested to reduce risk of relapse.